Exposure to persistent organic pollutants alters the serum metabolome in non-obese diabetic mice - Sinioja Tim; Bodin Johanna; Duberg Daniel; Dirven Hubert; Berntsen Hanne Friis; Zimmer Karin; Nygaard Unni C.; Orešič Matej; Hyötyläinen Tuula (SPRINGER, 2022)
Introduction
Autoimmune disorders such as type 1 diabetes (T1D) are believed to be caused by the interplay between several genetic and environmental factors. Elucidation of the role of environmental factors in metabolic and immune dysfunction leading to autoimmune disease is not yet well characterized.
Objectives
Here we investigated the impact of exposure to a mixture of persistent organic pollutants (POPs) on the metabolome in non-obese diabetic (NOD) mice, an experimental model of T1D. The mixture contained organochlorides, organobromides, and per- and polyfluoroalkyl substances (PFAS).
Methods
Analysis of molecular lipids (lipidomics) and bile acids in serum samples was performed by UPLC-Q-TOF/MS, while polar metabolites were analyzed by GC-Q-TOF/MS.
Results
Experimental exposure to the POP mixture in these mice led to several metabolic changes, which were similar to those previously reported as associated with PFAS exposure, as well as risk of T1D in human studies. This included an increase in the levels of sugar derivatives, triacylglycerols and lithocholic acid, and a decrease in long chain fatty acids and several lipid classes, including phosphatidylcholines, lysophosphatidylcholines and sphingomyelins.
Conclusion
Taken together, our study demonstrates that exposure to POPs results in an altered metabolic signature previously associated with autoimmunity.